A new treatment for presumed corneal epithelial inclusion cyst in a shih‐tzu dog. (23rd April 2019) - Kang, S.; Park, E.; Seo, K.
Abstract : An 8‐year‐old female shih‐tzu was assessed for a 3‐year history of yellow intrastromal material in the right eye. Slit‐lamp biomicroscopy showed a yellow lesion in the upper half of the cornea, superficial corneal neovascularisation and oedema with negative fluorescein staining in the right eye. Ultrasound biomicroscopy revealed a nearly anechoic cystic space surrounded by hyperechoic oedematous cornea separating the stroma at three‐quarters of the corneal depth. Two partial‐thickness corneal incisions were performed around the lesion under topical anaesthesia. After cytology and culture sampling, intrastromal flushing was performed. A yellow viscous necrotic tissue was identified with no microorganism or evidence of tumour formation. Antibiotics, anti‐inflammatories and a bandage contact lens were applied. Ultrasound biomicroscopy confirmed no recurrence 8 days later. Corneal neovascularisation and oedema gradually resolved through a 2‐week follow‐up. There was no recurrence in the subsequent 8 months.